2021
DOI: 10.3126/jnps.v41i3.37654
|View full text |Cite
|
Sign up to set email alerts
|

Utilization and Effectiveness of Free Newborn Care Service Package in Inpatient Care of Sick Newborns –A Time For its Revision to Ensure Sustainability: Evidences From a Tertiary Level Public Hospital in Nepal

Abstract: Introduction: Free Newborn Care (FNC) service has been implemented to address the financial barriers to access sick newborn care in Nepal. This study was designed to evaluate the effectiveness of FNC package in terms of its adequacy to support a facility financially and the factors to be considered for reimbursement schemes in the FNC guideline. Methods: This is a cross sectional retrospective study where 2907 newborns who received FNC service from 2019 Mar 15 to 2021 Jan 14 over 20 months were included. Descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
(23 reference statements)
1
1
0
Order By: Relevance
“…The nding from qualitative nding supports this nding, those households found close to the health facility with availability of health facility nearby households, and less distance from a health facility were the explored key barriers for community-based newborn care service utilization. This result of the study is supported by the study done in different regions of Ethiopia and Nepal (3,7,27). The possible justi cation for this might be due to those women who found in nearby to the health facility may have a greater chance of utilizing community-based newborn care services than those found in far and hard-to-reach areas.…”
Section: Health Facility Related Characteristicssupporting
confidence: 62%
See 1 more Smart Citation
“…The nding from qualitative nding supports this nding, those households found close to the health facility with availability of health facility nearby households, and less distance from a health facility were the explored key barriers for community-based newborn care service utilization. This result of the study is supported by the study done in different regions of Ethiopia and Nepal (3,7,27). The possible justi cation for this might be due to those women who found in nearby to the health facility may have a greater chance of utilizing community-based newborn care services than those found in far and hard-to-reach areas.…”
Section: Health Facility Related Characteristicssupporting
confidence: 62%
“…Previous studies revealed that maternal age, birth order, frequency of antenatal care use, place of delivery, gestation age at birth, presence of premature rupture of membrane, complication during labor, twin delivery, low birth weight, knowledge of the mothers on newborn danger signs and neonatal care practice were identi ed determinants of community-based newborn care service utilization (3,7,8,(12)(13)(14)27). Breastfeeding, new-born resuscitation, kangaroo mother care' for premature babies (prolonged skin-toskin contact with the mother), and preventing and treating infections are the most effective interventions in life-saving of the newborn in Ethiopia and implementing the key neonatal and child survival interventions (1,6,9,20,24).…”
Section: )mentioning
confidence: 99%